Multiplication operator on a matrix polynomial - Mikityuk , Ya. V.; Al-Tunzhi , M. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
It is proved that the study of a perturbed multiplication operator on a matrix polynomial in the space $L_2 (\mathbb{R}, \mathbb{C}^n)$ may be reduced to the study of a perturbed multiplication operator with independent variable in the space $L_2 (\mathbb{R}, ω, \mathbb{C}^N)$ with weight $ω$ satisfying the Mackenhaupt condition.